Biogenic amines and urocanic acid in keropok lekor, and their effects on cytotoxicity and proinflammatory mediator secretion of macrophage cell culture - Hussain, Husniza (2017)
Scombroid fish poisoning (SFP) or histamine fish poisoning (HFP) is caused by consumption of mishandled fish or fishery products containing high contents of histamine and leads to allergy-like reaction. Keropok lekor or Malaysian fish sausage is a widely consume fish product. In fish products, some spoilage indicators are used including the levels of biogenic amines (BAs), urocanic acid (UCA), and presence of microorganisms. This thesis work aimed to develop rapid and robust methods for quantification/screening of nine BAs, UCA isomers and amino acid decarboxylase-producing bacteria in keropok lekor processed at different stages. Furthermore, the cytotoxicity and induction of proinflammatory mediator secretion by individual or mixture of the investigated compounds were carried out on RAW 264.7 macrophage cell culture. The modified Ultra High Performance Liquid Chromatography enabled rapid verification measurement of BAs and UCA regardless of inclusion of internal standard. The validated Liquid Chromatography-Mass Spectrometry using high strength silica polyfluorophenyl column allowed simultaneous measurement of all investigated compounds. The Møller Decarboxylase Micro-Method for screening of BAs-producing bacteria showed cost-effectiveness with small volume of growth media used, less laborious with reduce waste disposal. The developed method for determination of simultaneous cells viability using multilabel microplate reader may serve as an alternative application of acridine orange and propidium iodide in addition to their common usage in confocal microscopy imaging. This study revealed that BAs levels did not increase following the heat treatment i.e. boiling and frying of the keropok lekor. Nonetheless, frying process was showed to be best eliminating the amino-acid decarboxylase-producing bacteria. Several microorganisms were identified in both the fresh and processed keropok lekor. These include Proteus vulgaris, Proteus mirabilis, Kocuria rhizophila, Kocuria kristinae, Lactococcus garvieae, Granulicatella elegans and Candida parapsilosis. The study on the effects of BAs on RAW 264.7 macrophage cell culture showed that individual tyramine, tryptamine, spermine and spermidine induced inflammation in the macrophages led to apoptosis and necrosis, but no progression of inflammation nor secretion of proinflammatory mediators were observed with the keropok lekor extracts and its BAs mixtures. Spermine and spermidine were the most cytotoxic and the inhibition concentrations at 50% cell viability (IC50) were 28.35 μg/ml and 56.01 μg/ml, respectively. Taken together, this thesis work develops several modified methods that are rapid and robust for quantifying and screening of BAs, UCA and microorganisms in fishery products i.e. keropok lekor. The study also suggests that effective heat treatment i.e. frying could improve the microbiological quality of keropok lekor but not the contents of BAs. In addition, different food-related BAs exhibit different cytotoxicity effects on the RAW 264.7 macrophage cell culture. Future research on in vitro cytotoxicity effects of BAs in fishery products or other foods using different cell lines to resemble in vivo study is warranted.